KONTRIBUSI KONDISI FISIK TERHADAP KETERAMPILAN BERMAIN CABANG OLAHRAGA PERMAINAN - Hulfian, Lalu (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Physical and technical conditions are two factors that support athletes to achieve peak performance. With good physical condition, athletes will be faster and more appropriate to use technical abilities and apply tactics given by a coach. Thus, achievement will certainly be obtained faster. However, the extent to which the physical condition contributes to the skills of the game's sport has not been known in more detail. The formulation of the problem in this study is how does the physical condition and playing skills of athletes playing sports contribute? The purpose of this study was to measure and analyze physical conditions and playing skills in sports. The research method used is correlational. Subjects in the study were 45 members of the IKIP Mataram Sports UKM. The sampling technique used was purposive sampling. The analysis technique with SPSS is multiple linear correlation. Based on the results of the research and discussion described in the previous chapter, the conclusions in this study can be stated as follows: (1). The physical condition of the PS IKIP Mataram players is in a very good condition (2). The skill of playing soccer PS IKIP Mataram is in the good category. (3). There is a relationship between the physical condition and the skill of playing football players PS IKIP Mataram